2007
DOI: 10.1074/jbc.m605031200
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin-binding Proteins Modulate the Susceptibility of Bacterial Endotoxin to Deacylation by Acyloxyacyl Hydrolase

Abstract: Acyloxyacyl hydrolase (AOAH) is an eukaryotic lipase that partially deacylates and detoxifies Gram-negative bacterial lipopolysaccharides and lipooligosaccharides (LPSs orLOSsTissue invasion by even minute quantities of many Gramnegative bacteria (GNB) 2 initiates rapid mobilization of the innate immune responses of the host. In these circumstances, both GNB recognition and many responses depend upon activation of the exquisitely sensitive Toll-like receptor 4 (TLR4) by endotoxins, structurally unique and abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
75
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(77 citation statements)
references
References 45 publications
2
75
0
Order By: Relevance
“…Acyloxyacyl hydrolase converts hexa-acylated endotoxins that are potent TLR4 agonists to tetra-acylated species that are TLR4 antagonists [3,105,106]. Endotoxin associated with intact bacteria and bacterial remnants is also partially deacylated in the extracellular inflammatory fluid [88] but at a much slower rate.…”
Section: Bpi Actions During Host: Gnb Interactionsmentioning
confidence: 99%
“…Acyloxyacyl hydrolase converts hexa-acylated endotoxins that are potent TLR4 agonists to tetra-acylated species that are TLR4 antagonists [3,105,106]. Endotoxin associated with intact bacteria and bacterial remnants is also partially deacylated in the extracellular inflammatory fluid [88] but at a much slower rate.…”
Section: Bpi Actions During Host: Gnb Interactionsmentioning
confidence: 99%
“…41 Finally, Gioannini et al recently found that LBP binds to LPS to expose fatty acyl chains within lipid A, which allows acyloxyacyl hydrolase and eukaryotic lipase to bind and detoxify LPS. 42 Although these data suggest that high levels of circulating LBP may be beneficial for curtailing the inflammatory response to high concentrations of LPS, the resultant attenuation of cellular response to GN bacteria, especially when leukocyte counts are already low and innate immunity is even more important in host defense (as commonly found early after transplantation), may permit unchecked GN bacterial growth and ultimately result in death.The association of SNP 1683 with a 5-fold increase in risk of death after transplantation among patients with GN bacteremia, and a borderline effect among patients without GN bacteremia, suggests several possible mechanisms by which LBP variants might influence mortality risk. This finding is consistent with the known biology of LBP and the major role it plays in modulating the host immune response to GN bacteria and LPS.…”
mentioning
confidence: 99%
“…41 Finally, Gioannini et al recently found that LBP binds to LPS to expose fatty acyl chains within lipid A, which allows acyloxyacyl hydrolase and eukaryotic lipase to bind and detoxify LPS. 42 Although these data suggest that high levels of circulating LBP may be beneficial for curtailing the inflammatory response to high concentrations of LPS, the resultant attenuation of cellular response to GN bacteria, especially when leukocyte counts are already low and innate immunity is even more important in host defense (as commonly found early after transplantation), may permit unchecked GN bacterial growth and ultimately result in death.…”
mentioning
confidence: 99%
“…On the basis of these and many other studies, we and others have proposed that potent TLR4-dependent cell activation by endotoxin depends on sequential protein-endotoxin and protein-protein interactions between endotoxin, LBP, CD14, MD-2, and TLR4 (1-4, 9 -11). Thus, LBP binds to endotoxin as presented natively in the bacterial outer membrane or as aggregates after extraction and purification (4,(12)(13)(14)(15). In so doing, LBP catalyzes delivery and transfer of individual molecules of endotoxin to CD14 (either as a soluble extracellular protein (sCD14) or GPI-linked membrane protein (mCD14)) (4,7,(13)(14)(15)(16).…”
mentioning
confidence: 99%